Nitrogen and sulfur doped carbon dots with aggregation-induced emission characteristic and application thereof in anti-counterfeiting and encryption ink and test paper
By using dithiosalicylic acid and formamide to prepare nitrogen-sulphur-doped carbon dots, the complexity and low yield of aggregation-induced luminescent materials are solved, and the preparation of advanced anti-counterfeiting and dual-encrypted fluorescent inks and test strips is realized. It has the characteristics of low cost, strong anti-counterfeiting and high stability.
Patent Information
- Application Number
- CN202411210861.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The synthesis of existing aggregation-induced luminescent materials is complex and has low yields, making it difficult to prepare on a large scale. In addition, traditional organic luminescent materials are prone to aggregation-induced quenching in solid or aggregated states, which limits their application scope.
Using dithiosalicylic acid and formamide as raw materials and acetic acid and ethanol as solvents, nitrogen-sulfur-doped carbon dots with aggregation-induced luminescence characteristics were prepared through ultrasonic and high-temperature reactions, which were used to prepare advanced anti-counterfeiting and dual-encrypted fluorescence. Ink and fluorescent test strips.
It realizes fluorescent materials with low cost, strong anti-counterfeiting and high stability performance, expands the application of carbon dots in the fields of anti-counterfeiting marking and encryption, and provides a wide range of application and good stability and durability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005020284310000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fluorescent nanomaterials and anti-counterfeiting technology, and specifically to the synthesis of nitrogen-sulfur-doped carbon dots with aggregation-induced luminescence properties using dithiosalicylic acid and formamide as raw materials and acetic acid and ethanol as solvents, and in particular to the application of the carbon dots in anti-counterfeiting and encrypted fluorescent inks and fluorescent test paper detection. Background Art
[0002] Carbon dots (CDs) are a new type of zero-dimensional carbon-based nanomaterials, mainly composed of sp 2 The hybrid carbon core and surface functional groups such as hydroxyl, carbonyl, carboxyl, and amino groups are composed, and the particle size is usually less than 10nm. Since carbon dots have special properties such as fluorescence, photoelectric properties, chemical stability, and low toxicity, and at the same time, the surface of carbon dots can be functionalized by introducing functional groups and other chemical modification methods, thus giving carbon dots more specific functions and applications, making carbon dots widely used in many applications such as biological imaging, fluorescent labeling, environmental monitoring, drug delivery, and photodynamic therapy.
[0003] A notable feature of carbon dots compared to other materials is that the synthesis methods are extremely simple and diverse. There are many methods for preparing carbon dots, which can be roughly divided into two categories: "top-down" and "bottom-up". "Top-down" refers to cutting or peeling large molecules or complex carbon structures (such as carbon nanotubes, graphene, carbon fibers) into small-sized carbon dots through a series of physical or chemical processing methods. It mainly includes arc discharge, laser ablation, electrochemical treatment and other methods. Although this method can control the structure and morphology of carbon dots to a certain extent, the synthesis steps are usually complicated and cumbersome, the cost is high and the yield is low, and it is difficult to prepare on a large scale.
[0004] "Bottom-up" is the opposite of "top-down". It is a method that uses smaller carbon materials to gradually assemble, dehydrate and carbonize to form large molecular weight carbon nanoparticles. The synthesis methods mainly include hydrothermal method, solvothermal method, microwave method, template method, etc. Among them, hydrothermal method and solvothermal method are deeply favored by experimenters because of their convenient operation, low cost and controllable parameters. In addition to using small organic molecules or oligomers as carbon sources, hydrothermal / solvothermal method can also use biomass macromolecules as precursor substances. Biomass has a wide range of sources, abundant raw materials, and is easy to achieve large-scale synthesis, thereby accelerating the progress of carbon dots from laboratory preparation to industrial preparation to meet the needs of large-scale industrial applications.
[0005] Organic light-emitting materials have shown broad application prospects in the field of light-emitting applications due to their advantages of low cost, low toxicity, structural diversity, and easy modification. However, traditional organic light-emitting materials are prone to aggregation-induced quenching (ACQ) in the solid or aggregated state. Aggregation-induced emission materials mainly include various tetraphenylethylene, thiole, anthracene compounds and their derivatives such as tetraphenylethylene (TPE), tetraphenylpyrazine (TPB), distyrylanthracene (DSA), etc., which significantly enhance the luminescence in the solid or aggregated state, and are named aggregation-induced emission (AIE). These compounds have a helical structure and have excellent thermal stability, modifiability, mechanical properties, signal amplification and other characteristics. At present, aggregation-induced emission materials have overcome the aggregation-induced quenching effect of traditional fluorescent molecules, and have the advantages of photoelectric stability, high luminescence efficiency, biocompatibility, high temporal and spatial resolution, etc., and have been widely used in the technology transformation of multiple aspects and platforms such as photoelectric sensing, bioimaging, medical diagnosis, and anti-counterfeiting labels. However, the synthesis of many AIE molecules currently requires multi-step reactions, involving the separation and purification of multiple intermediates, which increases the complexity of the synthesis and may also reduce the overall yield. In addition, precise control of the emission color of AIE materials (such as red shift or blue shift) may require complex molecular design and regulation, which increases the difficulty of material design. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a nitrogen-sulfur dual-doped carbon dot and a preparation method and application thereof. This study developed a nitrogen-sulfur doped carbon dot with aggregation-induced luminescence properties using dithiosalicylic acid and formamide as raw materials and acetic acid and ethanol as solvents. A fluorescent ink for advanced anti-counterfeiting and double encryption was prepared using the carbon dots. The carbon dots can be used as anti-counterfeiting inks and anti-counterfeiting test papers, and have manufacturing advantages such as low cost, strong anti-counterfeiting, high stability, and a wide range of applications, which is of great significance to the safety and credibility of the product.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0008] The present invention provides a nitrogen-sulfur doped carbon dot, characterized in that the preparation method of the nitrogen-sulfur doped carbon dot comprises the following steps:
[0009] (1) Dissolving dithiosalicylic acid and formamide in ethanol or acetic acid and subjecting to ultrasonication to obtain a mixed solution;
[0010] (2) The mixed solution obtained in step (1) is placed in a polytetrafluoroethylene-lined high-pressure reactor and reacted in an oven at 180-230° C. for 8-15 h; preferably at 200° C. for 10 h;
[0011] (3) After the reaction, the solution is cooled to room temperature and placed in a water bath for evaporation and drying to obtain solid carbon dots.
[0012] In the above technical solution, further, the molar ratio of dithiosalicylic acid to formamide is 1:3-5; preferably 1:4.
[0013] In the above technical solution, further, the ultrasonic time in step (1) is 8-15 minutes, preferably 10 minutes.
[0014] In the above technical solution, further, the drying in step (3) is volatilization drying at 85-95°C; the preferred temperature is 90°C.
[0015] In the above technical scheme, further, when step (1) is dissolved in ethanol, a red solid R-CDs is prepared; when step (1) is dissolved in acetic acid, a yellow solid Y-CDs is prepared.
[0016] In the above technical solution, further, the carbon dots have an AIE optical effect, and the AIE effect comes from disulfide bonds.
[0017] The present invention provides an anti-counterfeiting and double-encrypted fluorescent ink, the ink comprising the aforementioned carbon dots; preferably, the ink is prepared from an ethanol-water solution or an acetic acid-water solution of the carbon dots; the volume ratio of ethanol to the mixed solution is greater than 40%, and the volume ratio of acetic acid to the mixed solution is greater than 30%.
[0018] The present invention provides an anti-counterfeiting and double-encrypted fluorescent test paper, wherein the test paper is prepared by soaking filter paper in the aforementioned ink and drying, or spraying the aforementioned ink on the filter paper and drying; preferably, the test paper is prepared by soaking the filter paper in an R-CDs solution to obtain a red test paper.
[0019] The present invention provides the application of the aforementioned ink or test paper in the field of anti-counterfeiting detection of commodities or certificates, the field of information hiding and re-hiding, and information integrity verification; preferably, the application in anti-counterfeiting and encryption materials.
[0020] In the above technical scheme, further, the application of ink is: using ink to write on white paper, after the ink dries, no color is shown, and the written content can be identified by displaying the ink color under ultraviolet irradiation, and the ink shows different colors under ultraviolet irradiation after spraying ethanol, and then evenly spraying aqueous solution after the ethanol evaporates to restore the color when no ethanol is sprayed; the application of test paper is: on the test paper, write with ethanol or water, no color is shown after drying, and different colors are shown under ultraviolet irradiation.
[0021] The parameters of the fluorescence spectrophotometer in this study can be set as follows: scanning speed (1000 nm / min), excitation bandwidth (10 nm), emission bandwidth (10 nm), gain (medium, 650 V).
[0022] The carbon dots prepared above can be used to make fluorescent ink and fluorescent test paper for advanced anti-counterfeiting and double encryption. The process consists of the following steps:
[0023] R-CDs solution and Y-CDs solution were used as fluorescent inks to write simple letters on ordinary filter paper with a brush, and the fluorescence effect was observed under ultraviolet light. At the same time, deionized water and ethanol solution were put into a spray bottle for anti-counterfeiting detection. In addition, ordinary filter paper was soaked in R-CDs solution to prepare red fluorescent test paper, and ethanol and water were used to write on the test paper to observe the fluorescence changes.
[0024] In this study, hydrophobic R-CDs and Y-CDs were synthesized using dithiosalicylic acid and formamide as raw materials and ethanol and acetic acid as solvents. The carbon dots were converted in water and ethanol / acetic acid solution states to achieve reversible fluorescence color changes, thereby preparing fluorescent inks and fluorescent test papers for anti-counterfeiting and encryption. The carbon dots showed good selectivity and sensitivity, as well as good stability and durability. Therefore, the application of carbon dot anti-counterfeiting labels has been expanded, broadening the ideas for the further development of fluorescent carbon dots.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a new nitrogen-sulfur doped carbon dot and a preparation method thereof, wherein the obtained R-CDs and Y-CDs carbon dots have an AIE effect, and the AIE effect comes from the disulfide bonds of the carbon dots. The carbon dot R-CDs or Y-CDs of the present invention are dissolved in ethanol or acetic acid solution and used as ink, and play the role of anti-counterfeiting and encryption by displaying different colors under ultraviolet irradiation.
[0027] The carbon quantum dot fluorescent test paper prepared by the carbon dots of the present invention has a wide range of raw materials, is easily available and is green and economical; the preparation process of the carbon quantum dot fluorescent test paper is simple, no other toxic and complex chemical reagents are required, the paper has a certain sensitivity, and has high fluorescence intensity and quantum yield.
[0028] The carbon quantum dot fluorescent test paper prepared by the present invention can not only change color under ultraviolet light, but also change color through simple and easily available solvents such as water and ethanol, thereby achieving efficient information verification and hiding of key information, and effectively ensuring the authenticity and traceability of the product.
[0029] The carbon quantum dot fluorescent test paper of the present invention has a short detection time and can be operated at room temperature.
[0030] After the carbon quantum dot fluorescent test paper prepared by the present invention is exposed to a normal environment for one month, the carbon dots still remain stably on the filter paper surface and show a strong fluorescence effect under ultraviolet excitation. The R-CDs and Y-CDs placed in the filter paper carrier show good stability and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the preparation, dispersion and aggregation states of R-CDs and Y-CDs involved in the present invention and the anti-counterfeiting application of fluorescent ink;
[0032] Figure 2 Optical characterization results of R-CDs; (A) TEM image of R-CDs dispersed in ethanol; (B) HRTEM image of R-CDs dispersed in ethanol (inset: particle size distribution); (C) TEM image of R-CDs dispersed in water; (D) XRD image of R-CDs dispersed in water;
[0033] Figure 3 R-CDs spectrum; (A) is the FT-IR spectrum of R-CDs; (B) is the XPS spectrum of R-CDs; (C) is the high-resolution O1s spectrum of R-CDs; (D) is the high-resolution N1s spectrum of R-CDs; (E) is the high-resolution C1s spectrum of R-CDs; (F) is the high-resolution S2p spectrum of R-CDs;
[0034] Figure 4 Optical characterization of Y-CDs; (A) TEM image of Y-CDs dispersed in acetic acid; (B) HRTEM image of Y-CDs dispersed in acetic acid (inset: particle size distribution); (C) TEM image of Y-CDs dispersed in water; (D) XRD image of Y-CDs dispersed in water;
[0035] Figure 5 Y-CDs spectrum; (A) is the FT-IR spectrum of Y-CDs; (B) is the XPS spectrum of Y-CDs; (C) is the high-resolution O1s spectrum of Y-CDs; (D) is the high-resolution N1s spectrum of Y-CDs; (E) is the high-resolution C1s spectrum of Y-CDs; (F) is the high-resolution S2p spectrum of Y-CDs;
[0036] Figure 6UV-visible absorption, fluorescence excitation and emission spectra of R-CDs; (A) is the UV-visible absorption, fluorescence excitation and emission spectra of R-CDs solution (illustration: the color of the solution under UV and sunlight); (B) is the emission spectrum of R-CDs solution at different excitation wavelengths; (C) is the UV-visible absorption, fluorescence excitation and emission spectra of R-CDs powder (illustration: the color of the powder under UV and sunlight); (D) is the emission spectrum of R-CDs powder at different excitation wavelengths;
[0037] Figure 7 UV-visible absorption, fluorescence excitation and emission spectra of Y-CDs; (A) UV-visible absorption, fluorescence excitation and emission spectra of Y-CDs solution (illustration: the color of the solution under UV and sunlight); (B) emission spectrum of Y-CDs solution at different excitation wavelengths; (C) UV-visible absorption, fluorescence excitation and emission spectra of Y-CDs powder (illustration: the color of the powder under UV and sunlight); (D) emission spectrum of Y-CDs powder at different excitation wavelengths;
[0038] Figure 8 Example 4 Experimental results of R-CDs; (A) is an image of R-CDs in water-ethanol solutions of different ratios under ultraviolet radiation (upper) and sunlight (lower); (B) and (C) are spectra (λex=358 nm) and UV-visible absorption spectra of R-CDs in water-ethanol solutions of different ratios; (D) is the emission spectra of R-CDs in different solvents;
[0039] Fig. 9 Example 4 Y-CDs experimental results; (A) is the image of Y-CDs in water-ethanol solutions of different proportions under ultraviolet radiation (upper) and sunlight (lower); (B) and (C) are the spectra (λex=358 nm) and UV-visible absorption spectra of Y-CDs in water-ethanol solutions of different proportions; (D) is the emission spectra of Y-CDs in different solvents;
[0040] Fig.10 Comparison results of P-CDs and R-CDs; (A) is the comparison of P-CDs (upper figure) and R-CDs (lower figure) in solution and solid state; (B) is the Fourier transform infrared spectra of P-CDs and R-CDs;
[0041] Fig.11 The fluorescence lifetime results are shown in Figure 2; (A) Fluorescence lifetime of R-CDs in solution and solid state; (B) Fluorescence lifetime of Y-CDs in solution and solid state;
[0042] Fig.12The color development results of R-CDs and Y-CDs solutions; (A) is the image of filter paper treated with ethanol and water under fluorescent light and ultraviolet light; (B) is the multiple test cycles of anti-counterfeiting ink; (C) is the time stability of anti-counterfeiting ink;
[0043] Fig.13 Experimental results of fluorescent ink and test paper; (A) R-CDs and Y-CDs are used as fluorescent ink for simple writing; (B) R-CDs and Y-CDs are used as fluorescent test paper for simple writing. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0045] Example 1
[0046] Preparation of red solid R-CDs.
[0047] 0.306 g of dithiosalicylic acid and 160 μL of formamide were weighed at a molar ratio of 1:4, dissolved in 30 mL of ethanol, and ultrasonicated for 10 min to fully dissolve. The resulting mixture was placed in an oven at 200°C for 10 h. After the reaction solution was cooled to room temperature, it was transferred to a water bath for evaporation and drying to obtain red solid R-CDs, which was stored for later use.
[0048] Various optical characterization results of R-CDs are as follows:
[0049] Transmission electron microscopy characterization: Figure 2 The results of (A) show that the prepared R-CDs are spherical in ethanol solution, evenly dispersed, and have no obvious agglomeration. Figure 2 (C) shows that R-CDs dispersed in deionized water are black clumps, proving that they are aggregated in water. Figure 2 (A) The distribution histogram in the upper left corner shows that the particle size range is 2.20-7.25nm, with an average particle size of 4.21nm, showing a good normal distribution. Figure 2 (B) HRTEM shows that R-CDs have obvious lattice fringes with a spacing of 0.19 nm, which corresponds to the lattice spacing of graphite structure. Figure 2 (D) is the XRD analysis spectrum, which shows that there is a significant diffraction peak near 26°, corresponding to the (002) plane of graphite. The results of HRTEM and XRD both prove that R-CDs has a crystal structure similar to graphite.
[0050] Figure 3 The result of (A) shows 3068cm -1 Attributable to the stretching vibration of CH, 2674 cm -1 and 2561cm-1 The two strong absorption bands of 1687cm- -1 The significant absorption peak at 1423 cm is attributed to the stretching vibration of C=O. -1 and 1292cm -1 The sharp characteristic peak appears due to the stretching vibration of CN, 708cm -1 and 550cm -1 The nearby absorption peaks belong to CS and SS, respectively. Figure 3 (B) XPS spectrum analysis of the elemental composition and chemical bonding of R-CDs. Figure 3 The results of (A) are basically consistent. The four characteristic peaks centered at 163.72, 284.76, 399.94 and 532.13 are the binding energies of S2p, C 1s, N1s and O1s, respectively, indicating the successful doping of nitrogen and sulfur elements. Figure 3 The results of (C) show that the two characteristic peaks at 531.72 and 533.28 eV can be attributed to C=O and CO. Figure 3 The results of (D) show the main peaks of pyrrolic N and pyridinic N, corresponding to 400.3 and 399.24 eV, respectively. Figure 3 The results of (E) show that the characteristic peaks at 284.77, 286.2 and 288.65 eV are attributed to CC / C=C, CN and C=O, respectively. Figure 3 (F) shows that the two peaks at 163.52 and 164.45 eV correspond to SC and SS, respectively.
[0051] Example 2
[0052] Preparation of yellow solid Y-CDs.
[0053] 0.306 g of dithiosalicylic acid and 160 μL of formamide were weighed at a molar ratio of 1:4, dissolved in 30 mL of acetic acid, and ultrasonicated for 10 min to fully dissolve. The resulting mixture was placed in an oven at 200°C for 10 h, and after the reaction solution was cooled to room temperature, it was transferred to a water bath for evaporation and drying to obtain yellow solid Y-CDs, which was stored for later use.
[0054] Various optical characterization results of Y-CDs are as follows:
[0055] Transmission electron microscopy characterization: Figure 4 (A) Figure 4 (C) TEM images of Y-CDs dispersed in acetic acid and deionized water, respectively. It can be clearly observed that Y-CDs are dispersed in acetic acid solution and aggregated in deionized water. Figure 4(A) The distribution histogram in the upper right corner shows that the particle size range of Y-CDs is 2.4-7.01nm, with an average particle size of 4.08nm. Figure 4 (B) HRTEM shows that the nanoparticles have high crystallinity and a lattice spacing of 0.20 nm, corresponding to the (002) plane of graphene. Figure 4 (D) is the XRD analysis spectrum, which shows that there is a significant diffraction peak near 2θ=26°, which is also associated with the (002) plane of graphite. The characterization results of lattice spacing and diffraction peaks confirm that Y-CDs is a graphite structure with high crystallinity.
[0056] The functional groups of Y-CDs are similar to those of R-CDs. Figure 5 The results of (A) show that the infrared wavelengths are 3009, 1680, 739 and 553 cm -1 The characteristic peaks at 2654 and 2518 cm -1 There are SH stretching vibrations at 1415 and 1262 cm -1 There is stretching vibration of CN. Figure 5 As shown in (B), Y-CDs are composed of C, O, S, and N elements, with the proportions of each element being 70.43%, 15.84%, 10.82%, and 2.92%, respectively. Compared with R-CDs, the C element has slightly decreased, and the O element has slightly increased, but the overall difference is not large. Figure 5 The results of (C) show that there are two fitting peaks at 531.63 and 532.89 eV, representing C=O and CO, respectively. Figure 5 The results of (D) show that the peaks at 400.7 and 401.7 eV are attributed to graphite N and NH, respectively. Figure 5 The results of (E) show that two characteristic peaks were resolved at 284.78 and 288.9 eV, representing CC / C=C and C=O, respectively. Figure 5 (F) shows that the two peaks at 163.61 and 164.78 eV correspond to SC and SS, respectively.
[0057] Comparing the TEM, FT-IR and XPS spectra of R-CDs and Y-CDs, both carbon dots are aggregated in water and dispersed in acetic acid or ethanol. Considering that acetic acid is rich in carboxyl groups and ethanol contains more hydroxyl groups, except for a slight change in the content of C and O elements, the functional groups and chemical bonds of the two are almost the same.
[0058] Example 3
[0059] The optical properties of R-CDs and Y-CDs were investigated, and the UV-visible absorption spectra and fluorescence excitation and emission spectra of the solutions and powders of the two substances were tested respectively. Figure 6 (A) shows that the significant absorption peaks of R-CDs in ethanol solution at around 220nm and 306nm are caused by π-π* and n-π* transitions. Figure 6 (C) The solid powder of R-CDs shows different UV absorption at 560nm in addition to the same absorption peak at 306nm, which can be attributed to the n-π* transition of C=O, CO, and CS structures. The ethanol solution of R-CDs exhibits blue fluorescence, which appears light pink under sunlight, and the best emission peak is obtained at 382nm under the excitation wavelength of 358nm. Figure 6 (B) shows that when the excitation wavelength of the ethanol solution of R-CDs increases from 320nm to 440nm, the optimal emission peak gradually shifts, showing the excitation dependence phenomenon caused by the uneven correlation defects on the carbon dot surface. Figure 6 (C) Powdered R-CDs exhibit red fluorescence with an emission peak at 645 nm and an optimal excitation wavelength of 560 nm. Figure 6 (D) shows that after changing the excitation wavelength, the emission peak of R-CDs powder always remains around 645nm, with no excitation dependence, showing excitation-independent characteristics.
[0060] Figure 7 (A) The acetic acid solution of Y-CDs shows blue fluorescence, which is yellow under sunlight. The ultraviolet absorption peaks at 254 and 316 nm are attributed to the π-π* and n-π* transitions. Figure 7 (C) The solid state of Y-CDs shows yellow fluorescence. In addition to the absorption at 316nm, the shoulder peak at 450nm originates from the n-π* transition of C=O, CN and CS. To study whether the fluorescence emission wavelength of Y-CDs in solution and solid state depends on the excitation wavelength, its fluorescence properties under the excitation wavelength range of 320-440nm were tested. Figure 7 (B) The results show that the maximum emission of Y-CDs solution under 370nm excitation is about 464nm, showing excitation wavelength dependence. Figure 7 (D) shows that the Y-CDs solid state has an optimal emission peak of 605nm under an excitation wavelength of 550nm, with no excitation dependence and the characteristic of being relatively independent of the excitation wavelength.
[0061] Comparing the optical properties of R-CDs and Y-CDs, both solutions show blue fluorescence under ultraviolet light, which is excitation-dependent, while the solids show red and yellow fluorescence, respectively, which do not have excitation-dependent characteristics, which means that the luminescence center of R-CDs and Y-CDs in the solid state is single.
[0062] Example 4
[0063] The study evenly dispersed R-CDs and Y-CDs powders in different proportions of ethanol-water, acetic acid-water and solvents of different polarities, observed their color changes under UV light and sunlight, tested UV and fluorescence emission spectra, and explored the AIE optical effect of carbon dots. The ethanol used was anhydrous ethanol, and the acetic acid was anhydrous acetic acid.
[0064] Take 3mg R-CDs powder and disperse it in 5mL ethanol-water mixed solution. The fluorescence color changes to Figure 8 (A) When the volume ratio of ethanol to the mixed solution is ≤40%, the solution is in a suspended state and the suspension exhibits red fluorescence. When the volume ratio of ethanol to the mixed solution is greater than 40%, the solution is clear and transparent and exhibits blue fluorescence. Figure 8 (B) and Figure 8 (C) shows that as the proportion of ethanol decreases, the emission spectrum of the solution red-shifts from 382nm to 450nm, and the fluorescence gradually changes from blue fluorescence emission to red fluorescence. This is because the solubility of R-CDs in ethanol is limited, and the powder that is not completely dissolved in ethanol is difficult to dissolve in water, thus forming an aggregated state and producing red fluorescence emission. At the same time, the trend of increasing absorbance at 306nm in the UV-visible spectrum with increasing ethanol content also confirms this speculation.
[0065] 3 mg of R-CDs powder was dissolved in 5 mL of solvents of different polarities, which were xylene, acetone, ethanol, N,N-dimethylformamide, dimethyl sulfoxide and water in order of polarity. Figure 8 As shown in (D), although the emission peak does not undergo a regular red shift with the increase of solution polarity, it corresponds to the dispersion of R-CDs in the solvent. When the R-CDs powder is evenly dispersed, the solution basically exhibits blue fluorescence, with an emission peak near 382nm. When in an aggregated state, the emission peak exists at 450nm, and the solution exhibits red fluorescence. The above results show that R-CDs are insensitive to the polarity of the solution and exhibit different emission wavelengths and fluorescence color changes in different dispersion media. However, due to its hydrophobicity, as the water content of R-CDs increases, the blue fluorescence of the dispersed state is turned off, and the red fluorescence of the aggregated state is turned on, resulting in a red-shifted fluorescence emission peak and a decreased absorbance. This trend provides strong evidence for the existence of π-π stacking in carbon dots.
[0066] When Y-CDs powder is dispersed in acetic acid-water solutions with different ratios and solvents with different polarities, Y-CDs exhibit similar AIE luminescence effects. Fig. 9(A) shows that when the acetic acid content in the mixed system is ≥30%, the Y-CDs solution is a clear and transparent liquid with blue fluorescence. When the acetic acid content in the system is <30% and the water content gradually increases, the Y-CDs solution begins to separate the yellow powder to form a turbid liquid with a suspension, which exhibits yellow fluorescence. Fig. 9 (B) Fig. 9 (C) shows that as the acetic acid content decreases, the emission spectrum significantly red-shifts and the absorbance at 316 nm decreases. Fig. 9 (D) The results show that Y-CDs in solutions of different polarities also prove that the carbon dots in the dispersed state exhibit blue fluorescence, while the carbon dots in the aggregated state exhibit yellow fluorescence.
[0067] In summary, both R-CDs and Y-CDs have the AIE effect and are dispersed in ethanol or acetic acid solutions. As the water content increases, they change from a dispersed state to an aggregated state, emitting red and yellow fluorescence, respectively. Figure 2 and Figure 3 The TEM images of carbon dots dissolved in ethanol / acetic acid and water can further confirm this conclusion.
[0068] Example 5
[0069] Preparation of brown solid P-CDs.
[0070] Benzoic acid and formamide were accurately weighed at a molar ratio of 1:4, 0.122 g and 160 μL, dissolved in 30 mL of ethanol, and ultrasonically treated for 10 min to fully dissolve. The resulting mixture was placed in a 200°C oven for reaction for 10 h. After the reaction solution was cooled to room temperature, it was transferred to a water bath for evaporation and drying to obtain brown solid P-CDs, which was stored for later use.
[0071] Furthermore, the mechanism of the AIE effect of R-CDs and Y-CDs was studied. Generally speaking, the graphitized carbon core is composed of some conjugated molecules. The presence of the carbon core causes a wide range of emissions and contributes to the formation of excitation-dependent fluorescence properties. Figure 8 and Fig. 9 The typical excitation dependence is shown, so it is considered that the blue emission of R-CDs and Y-CDs in solution is generated by the graphitized carbon core. Since carbon dots have a certain hydrophobicity, aggregation and precipitation occur after adding water. The core of graphitized carbon undergoes aggregation-induced fluorescence quenching (ACQ) due to the π-π stacking effect of its conjugated system, so there is no blue light emission. According to comparative experiments, it is inferred that the π-π stacking effect comes from the disulfide bond. The preparation of P-CDs without disulfide bonds uses benzoic acid instead of dithiosalicylic acid, and ethanol is used as the solvent. Fig.10(A) The results show that P-CDs exhibit blue fluorescence emission in ethanol solvent, but no obvious fluorescence in the solid state, and P-CDs are easily soluble in ethanol and aqueous solution. R-CDs containing disulfide bonds exhibit blue fluorescence emission in solution and significant red fluorescence in the solid state. In addition, Fig.10 As can be seen in (B), there is a significant difference in the infrared contrast spectra of P-CDs and R-CDs at 550 nm, which proves that the AIE effect of R-CDs comes from the disulfide bond.
[0072] In addition, according to K r (radiation rate constant) and K nr (Non-radiative rate constant) calculation formula K r =QY / τ and K nr =(1-QY) / τ can also prove this conclusion. In the formula, QY is the photoluminescence quantum yield of carbon dots, τ is the fluorescence lifetime of carbon dots, Fig.11 The fluorescence lifetime diagram of carbon dots after fitting, the calculated values of R-CDs and Y-CDs in solution and solid are shown in Table 1 and Table 2. It can be seen from Table 1 and Table 2 that Kr of R-CDs and Y-CDs is slightly higher and Knr is significantly reduced in the solid state. This is consistent with the mechanism of restricted molecular motion in the AIE phenomenon, that is, in the aggregated state, the vibration and rotation of the chemical bonds within the AIE molecule are greatly restricted by the interaction of the surrounding molecules or natural physical constraints, resulting in the obstruction of the non-radiative transition path, and the luminescence channel is mainly concentrated on the radiative transition, resulting in the enhancement of luminescence efficiency. According to the above results, the appearance of blue light fluorescence is due to the π-π* transition. There are uneven defects on the surface of carbon dots in the solution state, resulting in different energy levels in the π-π* energy gap. The fluorescence emitted by each energy level is different, resulting in excitation-dependent blue light emission. At this time, the self-rotation of the disulfide bond is not hindered, and energy is exchanged through intramolecular rotation. The appearance of red or yellow fluorescence is due to the accumulation of conjugated structures inside carbon dots in the aggregated state, which inhibits the occurrence of π-π* transitions and limits the blue fluorescence emission. At the same time, since the stacked conjugated structures limit the rotation of disulfide bonds, their energy is difficult to release through their own rotation and radiates in a divergent form, thus forming red and yellow fluorescence.
[0073] Table 1 shows the QY, τ, Kr, and Knr parameters of R-CDs solutions and powders;
[0074]
[0075] Table 2 shows the QY, τ, Kr and Knr parameters of Y-CDs solution and powder
[0076]
[0077] Example 6
[0078] Based on the above characterization results, the reasons why R-CDs and Y-CDs produce different colors of solid-state luminescence under the same raw materials, temperature and reaction time but different reaction solvents are discussed. Figure 2 and Figure 3 TEM spectra show that the average particle size of R-CDs with ethanol as solvent is larger than that of Y-CDs with acetic acid as solvent, while the lattice spacing of graphite (002) plane is reduced, indicating that when the solvent changes from acetic acid to ethanol, the carbonization degree increases, the graphitization effect is more significant, and a quantum size effect is produced. Comparing the optical properties of the two carbon dots, the excitation / emission wavelengths of R-CDs in the solid state are 560 / 645nm, which are significantly red-shifted compared with Y-CDs. At the same time, the peaks of n-π* transitions related to C=O, CN and CS also undergo red-shift. Considering the reasons, the red-shift causes the reduction of the band gap energy, and the band gap transition caused by the red-shift of the emission wavelength theoretically proves the quantum size effect. These results show that since the boiling point of ethanol is lower than that of acetic acid, ethanol has a higher degree of carbonization at the same temperature, and the size effect caused by different degrees of carbonization is the main reason for adjusting the fluorescence wavelength and producing different colors of solid-state luminescence.
[0079] Example 7
[0080] Due to the excellent AIE properties of R-CDs and Y-CDs, they exhibit different fluorescence colors in the dispersed and aggregated states, so they are used as dual-switch mode inks for anti-counterfeiting technology applications. Fig.12 As shown in (A), an ethanol solution of R-CDs (0.2g R-CDs dispersed in 30ml anhydrous ethanol) was dispersed on the left side of the butterfly-shaped filter paper, and an acetic acid solution of Y-CDs (0.2g Y-CDs dispersed in 30ml anhydrous acetic acid) was dispersed on the right side. After drying, it was found that the butterfly did not undergo obvious color changes under sunlight. The left part showed red fluorescence under ultraviolet light, and the right part showed yellow fluorescence (since the filter paper showed blue under ultraviolet light, it showed superimposed colors in the picture). After 75% ethanol solution was evenly sprayed on the surface of the butterfly, both showed blue fluorescence. After drying, the aqueous solution was continued to be evenly sprayed, and the fluorescent color of the butterfly returned to the initial state of red and yellow fluorescence. After continuous rotation of spraying ethanol and aqueous solution, the butterfly did not change color under sunlight. Considering the reason, after spraying ethanol solution, the carbon dots changed from an aggregated state to a dispersed state, thus showing blue fluorescence emission. After continuing to spray aqueous solution, due to the hydrophobic agglomeration effect of the carbon dots, it turned back to an aggregated state.
[0081] Fig.12As shown in (B), the stability of the anti-counterfeiting mark created using R-CDs and Y-CDs solutions was analyzed for multiple cycles. After evenly spraying ethanol and water on the surface of the butterfly filter paper four times, it still showed an obvious color change effect. Although the fluorescent color was slightly weakened, considering the loss of carbon dots during the spraying process and the limited adhesion between the carbon dots and the filter paper, this change was still within the controllable range. In addition, the time stability of the filter paper after four cycles was investigated. After being exposed to a normal environment for one month, the carbon dots still remained stably on the surface of the filter paper and showed a strong fluorescence effect under ultraviolet excitation. The above results show that the R-CDs and Y-CDs placed in the filter paper carrier show good stability and durability, providing a reliable foundation for the anti-counterfeiting field and demonstrating potential application prospects in anti-counterfeiting markings.
[0082] Fig.13 As shown in (A), R-CDs and Y-CDs solutions were used as fluorescent inks to write on blank filter paper, "S, U" was written with R-CDs, and "P" was written with Y-CDs. After the ink dried, red fluorescence of "S, U" and yellow fluorescence of "P" were observed under ultraviolet light (since the filter paper appears blue under ultraviolet light, the superimposed colors appear in the picture). After ethanol was sprayed on the surface of the test paper, "SPU" all showed blue fluorescence. After the ethanol evaporated, the aqueous solution was evenly sprayed, and the red and yellow fluorescence reappeared.
[0083] R-CDs fluorescent test paper can be prepared by soaking ordinary filter paper in R-CDs ethanol solution. The paper shows light red fluorescence under ultraviolet light. "SPU" is written on the red fluorescent test paper with ethanol and water respectively. The "S, U" written by ethanol shows blue fluorescence, and the "P" written by water shows red fluorescence.
[0084] According to the above results, these two types of carbon dots can not only be used as invisible colorless fluorescent anti-counterfeiting inks, but can also be composited with filter paper to form fluorescent test paper. Not only can they change color under ultraviolet light, but they can also change color through simple and easily available solvents such as water and ethanol, thereby achieving efficient information verification and hiding of key information, effectively ensuring the authenticity and traceability of the product.
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, and are only for the convenience of ordinary technicians in the technical field to understand and use the invention rather than to limit it; people familiar with the technology in the field can still modify the specific implementation of the present invention or replace some technical features with equivalents; and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A nitrogen-sulfur doped carbon dot, characterized in that: The method for preparing nitrogen-sulfur doped carbon dots comprises the following steps: (1) Dissolving dithiosalicylic acid and formamide in ethanol or acetic acid and subjecting to ultrasonication to obtain a mixed solution; (2) the mixed solution obtained in step (1) is reacted at 180-230° C. for 8-15 hours; (3) After the reaction, the solution is cooled to room temperature and dried to obtain solid carbon dots.
2. The nitrogen-sulfur doped carbon dots according to claim 1, characterized in that: The molar ratio of dithiosalicylic acid to formamide is 1:3-5.
3. The nitrogen-sulfur doped carbon dots according to claim 1, characterized in that: The ultrasonic time in step (1) is 8-15 minutes.
4. The nitrogen-sulfur doped carbon dots according to claim 1, characterized in that: The drying in step (3) is performed by volatilization drying at 85-95°C.
5. The nitrogen-sulfur doped carbon dots according to claim 1, characterized in that: When step (1) is dissolved in ethanol, a red solid R-CDs is prepared; when step (1) is dissolved in acetic acid, a yellow solid Y-CDs is prepared.
6. The nitrogen-sulfur doped carbon dots according to claim 1, characterized in that: The carbon dots have an AIE optical effect, and the AIE effect comes from disulfide bonds. 7.An anti-counterfeiting and double-encryption fluorescent ink, characterized in that: The ink comprises the carbon dots according to any one of claims 1 to 6; preferably, the ink is prepared from an ethanol-water solution or an acetic acid-water solution of the carbon dots; the volume ratio of ethanol to the mixed solution is greater than 40%, and the volume ratio of acetic acid to the mixed solution is greater than 30%. 8.An anti-counterfeiting and double-encrypted fluorescent test paper, characterized in that: The test paper is prepared by soaking filter paper in the ink of claim 7 and drying, or spraying the ink of claim 7 on the filter paper and drying; preferably, the test paper is prepared by soaking the filter paper in R-CDs solution to obtain a red test paper.
9. Application of the ink described in claim 7 or the test paper described in claim 8 in the field of anti-counterfeiting detection of commodities or certificates, information hiding and re-hiding, and information integrity verification; preferably, application in anti-counterfeiting and encryption materials.
10. The use according to claim 9, characterized in that: The application of ink is as follows: use ink to write on white paper. After the ink dries, it does not show any color. The written content can be identified by displaying the ink color under ultraviolet irradiation. After spraying ethanol, the ink will show different colors under ultraviolet irradiation. After the ethanol evaporates, spray the aqueous solution evenly to restore the color when no ethanol is sprayed. The application of test paper is as follows: write on the test paper with ethanol or water. After drying, it does not show any color. It will show different colors under ultraviolet irradiation.
Citation Information
Patent Citations
Preparation method of two-color aggregation-induced emission algae carbon quantum dots
CN115074124A
Preparation method of multicolor fluorescent carbon dots with aggregation-induced emission characteristic
CN117285932A
Novel sulfur and nitrogen co-doped carbon dot as well as preparation method and application thereof
CN117844478A
